Course of infection and development of immunity in experimental infection of mice with Listeria serotypes. - von Koenig, C H (1983)
NMRI mice were experimentally infected with Listeria monocytogenes serotypes 1/2b, 3a, 4b, and 4d and Listeria innocua serotype 6b by different means. The course of infection was monitored, using bacteriological and histological methods. The following typical features of experimental infection with the various L. monocytogenes and L. innocua serotypes were observed. (i) On the basis of the mean lethal dose, L. monocytogenes 4b, 4d, and 1/2b proved to be mouse pathogenic, although to different degrees, L. monocytogenes 3a and L. innocua can be regarded as nonpathogenic for NMRI mice. The virulence of L. monocytogenes serotype 4d was increased 1,000-fold after adaptation to mice. (ii) Primary infection with any serotype of L. monocytogenes or L. innocua resulted in protection against a lethal challenge with the most virulent serotype, 4b. This protective immunity could be transferred by spleen cells. Compared with the duration of immunity achieved by infection with L. monocytogenes serotype 4b, the protection induced by infection with L. innocua was short lived and dose dependent. The data obtained also suggest that immunity after experimental infection with any serotype of L. monocytogenes or L. innocua is produced only when the animal host is filled with bacteria. (iii) The distribution of the germs in the internal organs of the mouse shortly after infection was dependent on the route of infection rather than on the serotype used. (iv) The main difference among the Listeria serotypes tested was their ability to multiply within the host and to induce a granulomatous inflammation. The results indicate that mouse pathogenicity and virulence of Listeria spp. cannot be defined only by the capacity of the bacteria to infect or kill conventional mice. Such a definition should include an analysis of the immune system of the host, a kinetic study of experimental infection, and a histomorphological evaluation of the lesions induced.